If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -6b = 2x + 10y Reorder the terms: -6b + 5x = 2x + 10y Solving -6b + 5x = 2x + 10y Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-5x' to each side of the equation. -6b + 5x + -5x = 2x + -5x + 10y Combine like terms: 5x + -5x = 0 -6b + 0 = 2x + -5x + 10y -6b = 2x + -5x + 10y Combine like terms: 2x + -5x = -3x -6b = -3x + 10y Divide each side by '-6'. b = 0.5x + -1.666666667y Simplifying b = 0.5x + -1.666666667y
| 10x^2+10xy+16y= | | 10x^2+10xy+16= | | 10x^2+10xy+16y^2= | | x^2-11x+10=-2x+2 | | -6x^2-4=0 | | 10x^4-20xy+16y^4= | | b-19=19 | | 10x^4-20xy-16y^4= | | -54=k+6 | | -8x-5x=-96 | | 36x^9+120x^12+84x^3=0 | | 5x+10+8=3-10x-30 | | 8.3m+19.4=-12-3.7m | | 5x-6b=2x+10 | | x^2+2+1=9 | | 4m^2-3m-27=0 | | 7=t+4 | | 5x-12=2x+21 | | 5x-11=2x+21 | | Y=3sinx^2 | | x^3+7x^2+8x-4=0 | | 5(w-72)-31=49 | | 2lnx+3=6 | | (3x-2y)(4x-5y)= | | (3x+.5)+(-7x-4.5)= | | (X+3)*2=X+3+8 | | x^3=1.068 | | (x+5)+2=10 | | -0.4(j+8)+3=1 | | 3p^2=-6 | | Rt+rst=0 | | -2+9n^2=98 |